Effect of dietary Extracellular polymeric substances from Lactic acid bacteria on disease resistance and immune response in the whiteleg shrimp (Litopenaeus vannamei) - Nguyen Huu Thanh; Trinh Thi Lan; Nguyen Thi Thuy Hang; Nguyen Huu Yen Nhi; Nguyen Phu Tho (Veterinary Integrative Sciences)
Extracellular polymeric substances (EPSs) are known to have prebiotic properties, promoting the growth of beneficial bacteria in the intestinal tracts of humans and animals. To investigate the prebiotic potential of EPSs isolated from lactic acid bacteria (LAB), specifically Lactiplantibacillus plantarum and Bifidobacterium bifidum, the study examined changes in intestinal LAB and Vibrio parahaemolyticus populations, as well as immune responses in the Pacific white shrimp, Litopenaeus vannamei. The results showed that dietary supplementation with EPSs increased the population of LAB while reducing the level of V. parahaemolyticus in the shrimp gut. Additionally, EPSs were found to enhance the cellular immune responses of the shrimp, including total haemocyte count, respiratory bursts, phenoloxidase activity, and superoxide dismutase activity. Shrimp that were not fed EPSs and later inoculated with V. parahaemolyticus registered a mortality rate of 91%. In contrast, shrimp fed with EPSs showed greater resistance to V. parahaemolyticus, with mortality rates ranging from 27-30% post-infection. These findings suggest that EPSs produced by LAB could be utilized as a potential prebiotic substitute for antibiotics in shrimp feed to inhibit the growth of V. parahaemolyticus, a significant pathogen in aquaculture. The prebiotic and immune-enhancing properties of EPSs demonstrated in this study highlight their potential as a sustainable and eco-friendly approach to disease management in shrimp farming.